Mathematics
charl99
13

Solve:   -3x + 6y = 123  9x - 7y = -226

+1
(2) Answers
Kaytlyn

From the first equation: -3x = -6y +123 Subtract 6y from both sides x = 2y - 41 Divide by -3 Substitute above into the second equation: 9(2y - 41) - 7y = -226 18y - 369 - 7y = -226 11y = 143 Add 369 y = 13 Divide by 11 Then substitute y back into the first equation -3x + 6*13 = 123 -3x + 78 = 123 -3x = 45 x = -15 Hope that helps

haylerzzzz

-3x + 6y = 123  9x - 7y = -226 -3x+6y= 123 (multiply both sides by 9).............1 9x - 7y = -226 (multiply both sides by -3).............2 eq (1) substitute - eq (2)                                      - 27x+54y=1107                                       -27x+21y=678                                (-)                           ................................................                                               33y=429                                                  y=13 if y=13 then x is -3x+6y= 123 = -3x+(6X13)=123     x=   (123- 78)/(-3) =-15 so the answer is x=-15 and y=13                               

Add answer